Antimicrobial use in 22 U.S. beef feedyards: 2016–2017. Issue 1 (17th November 2020) - Hope, Katie J.; Apley, Michael D.; Schrag, Nora F. D.; Lubbers, Brian V.; Singer, Randall S.
Abstract: This study describes antimicrobial use in 22 U.S. beef feedyards by use of two metrics: milligrams of antimicrobial per kilogram of liveweight sold (mg/kg‐LW) and antimicrobial regimens per animal year (Reg/AY). The primary objectives were to determine the feasibility of collecting antimicrobial use data at the level of the production system and to identify factors unique to feedyard systems which may confound interpretation of summarized antimicrobial use measures. Records were accessed directly from feedyards or through a data intermediary and then subjected to a process of standardization and quality assurance. Use is reported at the study level with all individual cattle lots from all feedyards combined, as well as at the feedyard level where values were first calculated for each feedyard and then expressed as means, standard deviations and median values. Use at the study level is first reported by antimicrobial class and then by antimicrobial class within the use categories of in‐feed, control of bovine respiratory disease (BRD) and individual animal treatment. Due to wide variations of antimicrobial class within use category, feedyard level antimicrobial use is reported only by antimicrobial class. Use values for medically important and not medically important antimicrobial classes are reported separately. Regimens are described for each antimicrobial class within use category by milligrams per regimen and by timeframe from first to last administration. The authors' selection of measures reported here was driven by a desire to minimize necessary assumptions, resulting in transparent reporting of values which can be directly related back to the factors within feedyard systems which may have influenced calculations. Reporting the number of regimens stratified by antimicrobial class within use category and then describing the characteristics of the reported regimens (milligrams per regimen and timeframe) optimize these objectives for reporting.